2021
DOI: 10.9734/sajrm/2021/v10i430237
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Assessment of Elechi Creek Receiving Wastewater Effluents from Industrial Operations in Port Harcourt City

Abstract: Disposal of wastewater and other effluents into water bodies from activities around water bodies have for long been of major concern and challenge to the environment leading to several infectious diseases. The amount of industrial untreated solid wastes from companies, wastewater from car washing activities, open drainages and agricultural runoffs located close to Elechi creek constitutes the wastewater effluents received by the creek thus resulting in the imbalance of the ecosystem. The study was therefore ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…The bacterial and fungal counts in this work within the range reported by Unimke et al [34] at Imo river estuary where the range was 2.23-2.39 x10 6 and 1.17-1.38 x10 5 cfu/ml, respectively for bacteria and fungi. Ogbonna et al [35] reported higher total bacteria counts (1.12±0.13x10 8 to 1.28±0.09x10 8 cfu/m) in surface water. The bacteria and fungi isolated and identified in this study are similar to those reported by several researchers in similar ecosystems [26,36,37].…”
Section: Discussionmentioning
confidence: 93%
“…The bacterial and fungal counts in this work within the range reported by Unimke et al [34] at Imo river estuary where the range was 2.23-2.39 x10 6 and 1.17-1.38 x10 5 cfu/ml, respectively for bacteria and fungi. Ogbonna et al [35] reported higher total bacteria counts (1.12±0.13x10 8 to 1.28±0.09x10 8 cfu/m) in surface water. The bacteria and fungi isolated and identified in this study are similar to those reported by several researchers in similar ecosystems [26,36,37].…”
Section: Discussionmentioning
confidence: 93%